Odpowiedzi

2010-04-08T18:20:50+02:00
A) n=k/7

b) k=a-6

c)-y=z-7
y=-z=7

d)d-a=bc/b
d-a÷b=c

e) x-1=2k /2
x-12=k

F) 2k-5=7n /7
2k-5/7=n
2010-04-08T18:26:41+02:00
A)k=7n
k:7=7n:7
n=k:7
b)a=k+6
a-6=k+6-6
k=a-6
c)z=7-y
z-7=7-y-7
-y=z-7
-y*(-1)=(z-7)*-1
y=-z+7
d)d=a+bc
d-a=bc
c=(d-a):b
e)x=2k+1
2k=x-1
k=(x-1):2
f)2k=7n+5
7n=2k-5
n=(2k-5):7
2010-04-08T18:27:52+02:00
A
k=7n:n
k:n=7*k
n=7k
B
a=k+6
-k=6-a/:(-1)
k=-6+a
C
z=7-y
y=7-z
D
d=a+bc/:c
d:c=a+bc:c
d:c=a+b/*d
d:c*d=a+b:d
c=a+b:d
E
x=2k+1/:k
x:k=2k+1:k
x:k=2+1/*x
x:k*x=x(2+1)
k=x(2+1)
F
2k=7n+5/:n
2k:n=7n+5:n
2k:n=7+5/*2k
n=2k(7+5)